Study of enzyme purification method and growth pattern for Pseudomonas putida in mercury removal - Abdul Aziz, Mohd Azoddein; Siti Nur Baizura, Yusuf; Faten Ahada, Mohd Azli; Ahmad Bazli, Bustary; Mariah, Che Mamat; Nur Athirah, Mohammad Basir (2018)
Mercury is one of the toxic element and very harmful. The exposure of the mercury will mainly cause health effect and the exposure can be in term of dose, age of person exposed, duration exposed route exposed and duration of exposed. In Malaysia, Mercury is one of the heavy metals of concern, found in wastewaters coming from oil refinery and petrochemical industries. Mercury and mercurial compounds are highly toxic contaminants in the aquatic systems and soils. The proper disposal of wastewater should be implement with the Department of Environment of Malaysia (DOE) which is the concentration of mercury should be 0.05 ppm for standard B in wastewater for the sake of people and environment health. There are many types of mercury removal technology to reduce the concentration of mercury such as chemical treatment, ion exchange, membrane filtration, adsorption as well as bioremediation which used for mercury removal in this study. This paper present the activity of enzyme from Pseudomonas putida (P. putida) is produced in the mercury treatment from petrochemical wastewater at optimum condition. P. putida growth at optimum condition in mercury different concentration was observed. Conclusion optimum condition concentration of mercury and shaker speed at 7 ppm is 41 ˚C and 180 rpm respectively, with able to reduce 92.59 % mercury concentration. During the processes of mercury removal, mercuric reductase was produced at value of 56 kDa.